2008
DOI: 10.1159/000119716
|View full text |Cite
|
Sign up to set email alerts
|

Mesangial Proliferative Glomerulonephritis with or without IgA Deposits: The Morphological Characters in Psoriasis Vulgaris

Abstract: Background/Aim: Chronic glomerulonephritides associated with psoriasis vulgaris have been reported in the literature. However, because of the limited number of cases and the lack of specific histological findings, the existence of psoriatic nephropathy remains controversial. This study was performed to investigate the clinical and morphological characteristics of renal involvement in psoriasis vulgaris. Methods: We studied retrospectively 11 patients with psoriasis vulgaris. All patients had nephritic urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…[40][41][42][43][44] Minimal nephrotic syndrome changes were also shown to precede or occur simultaneously with psoriasis in a case series of children. [40][41][42][43][44] Minimal nephrotic syndrome changes were also shown to precede or occur simultaneously with psoriasis in a case series of children.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[40][41][42][43][44] Minimal nephrotic syndrome changes were also shown to precede or occur simultaneously with psoriasis in a case series of children. [40][41][42][43][44] Minimal nephrotic syndrome changes were also shown to precede or occur simultaneously with psoriasis in a case series of children.…”
Section: Discussionmentioning
confidence: 87%
“…Prior small case studies have suggested that various types of GN, such as IgA nephropathy, membranous glomerulopathy and focal segmental glomerulonephritis, may be more likely to occur in patients with psoriasis. [40][41][42][43][44] Minimal nephrotic syndrome changes were also shown to precede or occur simultaneously with psoriasis in a case series of children. 45 Moreover, because GN may progress to CKD or late stage CKD (ESRD) and the diagnosis of CKD is made on the basis of abnormal urinalysis and glomerular filtration rate results without knowledge of the specific cause, 46 we further investigated the relationship among GN, ESRD and psoriasis.…”
Section: Discussionmentioning
confidence: 87%
“…Nephropathy associated with psoriasis has been increasingly reported in recent years. These kidney diseases include IgA nephropathy [29, 30], MN [1114], membranoproliferative glomerulonephritis [31], focal segmental glomerulosclerosis [32], minimal change disease [33], AA-amyloidosis [34], and therapy-related tubular-interstitial alteration [26]. …”
Section: Discussionmentioning
confidence: 99%
“…[7,8] Elevations in inflammatory markers such as CRP have also been associated with renal involvement. [10,17] However, these studies have not been confirmed through further investigations.…”
Section: H Akoglu Et Almentioning
confidence: 90%
“…[9] However, pathological evidences supporting any immunologic mechanisms common for these two entities have not been demonstrated yet. [10] Other glomerular lesions including membranous glomerulopathy and nephropathies due to nephrotoxic effects of systemically active medications administered for the treatment of psoriasis are quite rare in psoriatic patients. [11][12][13][14] The exact pathogenetic mechanisms of these entities remain unclear because of the limited number of cases.…”
Section: H Akoglu Et Almentioning
confidence: 99%